Errors in Patients’ Information Leaflets of Marketed Medicines in Pakistan - Adeel Arsalan, Sameer Qureshi, Mehtab Alam, Sadia Ahmed, Osama Shakeel, Anwar Ali, Wardah Jabeen (Journal of Applied Pharmaceutical Science, 2015)
The curing of patient is the top most priority of health associated professionals. Complete and proper information of medicine is always the willing of the patients and their close ones. The primary source of information for patients’ regarding the medicine is patients’ information leaflet (PIL). The main aim of the present study is to evaluate the errors and incomplete information in leaf inserts sold with marketed medicines in Pakistan. For the present study, 11 different classes of oral medicines of different multinational and national pharmaceutical industries were purchased from different community and hospitals pharmacies in Karachi. The present study has been revealed incomplete information related to medicines in PILs. 9 out of 11 PILs have 48.84% (n= 63) major while minor errors were 51.16% (n= 66). The major errors were included incomplete information of indications, adverse drug effects, drug mechanism, dosage errors, drug-drug and drug-food interactions, precautions and warning, pharmacokinetic profile and pregnancy and lactation. Whereas, omission of structural formula, molecular formula, molecular weight, chemical names, laboratory tests, clinical trials data, font size, paper quality, and use of national language (Urdu) have been observed as minor errors. It has been concluded that majority of PILs sold with marketed medicines were not up to the mark and met the regulatory requirements. In countries like Pakistan, with high illiteracy rate and low financial status, patients’ were unaware about the importance of PILs. Mainly pharmaceutical industries have not called attention on information of marketed drugs medicines in Pakistan which has been proven a shocking situation regarding the negligence of healthcare matter in Pakistan.
Keywords: Patients information leaflet, Errors,Pharmacovigilance, Incomplete information, Negligence.